How important is homeland education for refugees' economic position in the Netherlands? - Joop Hartog; Aslan Zorlu (Institute for the Study of Labor (IZA), 2005)
We use data on refugees admitted to the Netherlands that include registration of education in their homeland by immigration officers. Such data are seldom available. We investigate the quality and reliability of the registrations and then use them to assess effects on refugees' economic position during the first five years after arrival. The most remarkable finding is the absence of returns to higher education.
Keywords: I21; J31; J61; 330; immigrants; refugees; education; earnings; employment; Bildungsniveau; Flüchtlinge; Lohnniveau; Berufliche Integration; Niederlande